The Effect of Positive Affirmations to Anxiety level and 2nd stage of labor length - Rahayu, Esty Puji; Rizki, Lailatul Khusnul (STRADA : Jurnal Ilmiah Kesehatan, 2020)
The maternal mortality rate by sectio caesarea was 40-80 per 100,000 live births. Secto Cesarean can occur because the mother herself is not sure of her ability to normal birthing. Positive affirmations made by mothers are believed to be one of the supports so that mothers are sure that they can give birth normally and reduce anxiety about childbirth. This type of research is observational analytic with a quasi-experimental design, the type of post test only group design. Based on the results of data analysis with the T test, it was found that there was an effect of giving Positive affirmation on anxiety and 2nd stage of labor with p = 0.000 (p <0.05). Positive affirmation with flashcard affirmation greatly affects the level of anxiety of mothers in labor and it is easier to self-affirm so that negative thoughts about childbirth will be reduced